Determinação da idade e crescimento da piramutaba Brachyplatystoma vaillantii (Valenciennes, 1840) (Siluriformes : Pimelodidae) capturada no Estuário amazônico - PIRKER, Lilianne Esther Mergulhão (Universidade Federal do Pará, 2013)
The specimens of piramutaba (Brachyplatystoma vaillantii) analyzed in this research were obtained from experimental fisheries in the amazon estuary. For the study of age determination pectorals and dorsal spines, opercules, otoliths (lapillus) and vertebrae were analyzed. From the analysis of these structures it was concluded that the vertebrae is the most appropriate bony structure for the age determination of piramutaba. This is so because the vertebrae showed good resolution in annulus (59%), and it also has a significant exponential relationship (r² = 0,9889 and P<0,05) between the radius of the vertebrae and the fork length of fish. The seasonal rings were validated using length frequency analysis. Two annual rings are formed on the vertebrae of piramutaba. The weight-length relationship seen in piramutaba describes its growth as allometric and the equation that describes its growth is: Wt = 6,1 * 10-6 * Lf3,1129. The sexual proportion of piramutaba observed was not 1:1, as the number of females was superior to the males. On vertebraes of piramutaba a maximum of ten rings were observed. The von Bertalanffy growth model was utilized in this research to estimate the length and weight equations. The growth parameters (k, t0 e L∞) were estimated through four different methods: rings reading, backcalculation, rings modal progression and length frequency analysis. The growth parameters were k = 0,138 ano-1, t0 = -0,239 e L∞ = 110,5 cm (tings xeaffing); k = 0,119 ano-1, t0 = -0,202 e L∞ = 110,5 cm (backcakulation); k = 0,096 ano-1, t0 = -0,146 e L∞ = 110,5 cm (rings modal progression) and k = 0,127 ano-1, t0 = -0,236 e L∞ = 110,5 cm (length frequency analys is).